(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize contemporary evidence on how obesity, diabetes mellitus, and smoking influence perioperative and longer‑term outcomes after spine surgery, and to highlight practical optimization strategies. Methods: A narrative review of recent systematic reviews, meta‑analyses, guidelines and large cohort studies published mainly from 2016-2025 was conducted via PubMed and major spine journals. Key outcomes included surgical site infection, pulmonary and renal complications, pseudarthrosis/nonunion, reoperation, length of stay, and patient‑reported outcomes. Results: Obesity is associated with higher nonunion rates and worse patient‑reported outcomes following lumbar fusion, with increased perioperative events in many - but not all - procedures. Diabetes confers higher risks of surgical site infection and medical complications after fusion and other spine procedures; elevated preoperative HbA1c (7.5-8.0%) correlates with higher infection risk and poorer recovery. Smoking robustly increases pseudarthrosis and adverse outcomes after fusion; preoperative smoking cessation of at least four weeks reduces infectious, wound, and pulmonary complications. Enhanced recovery after surgery pathways support risk factor optimization and have demonstrated benefits in spine care. Conclusions: Obesity, diabetes, and smoking adversely affect spine surgery outcomes, especially fusion biology and infection risk. Prehabilitation bundles incorporating weight management, glycemic optimization (target HbA1c ≤ 7.5% when feasible), and verified smoking cessation ≥ 4 weeks should be prioritized to improve outcomes.